The Influence of Person Job Fit on Employee Engagement at PT Bank Nagari Pasar Raya Branch, Padang City, Mediated by Job Satisfaction - Gaza, Muhammad Rahman; Andriani, Chichi (Human Resource Management Studies, 2024)
The purpose of this study was to examine: (1) The effect of Person Job Fit on Employee Engagement in employees of PT Bank Nagari Pasar Raya Branch, Padang City, (2) The effect of Job Satisfaction on Employee Engagement in employees of PT Bank Nagari Pasar Raya Branch, Padang City, (3) The effect of Person Job Fit on Job Satisfcation in employees of PT Bank Nagari Pasar Raya Branch, Padang City, (4) The effect of Person Job Fit on Employee Engagement mediated by Job Satisfaction in employees of PT Bank Nagari Pasar Raya Branch, Padang City. This form of research is quantitative research. The sampling technique was a total sampling technique with 43 respondents sampled for this study. Direct questionnaire distribution was used to collect data, and PLS tools were used for data processing in this study. The results of this study indicate that: (1) Person Job Fit has a positive and significant effect on Employee Engagement in employees of PT Bank Nagari Pasar Raya Branch, Padang City, (2) Job Satisfcation has a positive and significant effect on Employee Engagement in employees of PT Bank Nagari Pasar Raya Branch, Padang City, (3) Person Job Fit has a positive and significant effect on Job Satisfaction in employees of PT Bank Nagari Pasar Raya Branch, Padang City, (4) Person Job Fit has a positive and insignificant effect on Employee Engagement mediated by Job Satisfaction in employees of PT Bank Nagari Pasar Raya Branch, Padang City.